Pemimpin Ideal Perspektif Al-Qur'an - Dozan, Wely; al Basir, Qohar (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2021)
Islamic leadership stands on divine leadership (ketauhidan), that every human being is only submissive and obedient to the leader of Allah SWT. The character of a leader in Islam has its own characteristics, because in Islam it carries a very large mission in bringing the values ​​of Islamic teachings. The Al-Qur'an has universally regulated various aspects of life, one of which is the concept of an ideal leader in order to create peace and tranquility in people's lives. Islam views that humans are born on earth to become caliphs according to the basis of the Al-Qur'an which has been outlined. This paper is here to explore several verses that specifically discuss leadership and provide the objectives and characteristics that must be possessed in realizing the concept of an ideal leader in the perspective of the Qur'an. The author formulates several concepts and characteristics possessed by ideal leaders including, First, Al-Ilm (People who are knowledgeable. Second, Mujahid (People who always struggle). Third, Mutay (People who always sacrifice. Fourth, a caliph has the potential even in a actually can keep lust in doing leadership Fifth, Mutajarrid (People who totality).